REPRESENTASI IDENTITAS MAHASISWA MELALUI GAYA BERPAKAIAN DI TIKTOK (STUDI KASUS MAHASISWA FAKULTAS AGAMA ISLAM UNIVERSITAS MUHAMMADIYAH BENGKULU) - Resita, Resita Aprelia Sanjaya; Amrullah; Heriyanti, Lesti (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
The purpose of this study is to understand how students of the Faculty of Islamic Religion (FAI) at Universitas Muhammadiyah Bengkulu (UMB) express their identity through dressing on TikTok. In this digital age, social media platforms have become an important means for people to express themselves, their identity, as well as their social values. This research uses a qualitative approach with a case study method, involving five active FAI-UMB students who frequently visit content on TikTok. Data sources were obtained through observation, interviews, and documentation. The results of this study show that the way FAI-UMB students dress on TikTok not only reflects their academic and religious identities, but is also influenced by fashion trends and personal desires. This identity can be seen from the choice of colors, clothing models, and uploaded content that combines Islamic values with innovative visual representations. This research draws on the theory of symbolic interactionism, which explains how individuals display identity through social interaction and the use of symbols, such as clothing. For example, clothing can serve as a medium of identity communication to create meaning. In conclusion, TikTok serves as a strategic platform for FAI-UMB students to form and express a complex identity, which is a combination of religious values, pop culture, and personal desire to be seen.